Asymmetric information, corporate finance, and investment - Hubbard, R. Glenn (Project report (National Bureau of Economic Research), 1990)
In this volume, specialists from traditionally separate areas in economics and finance investigate issues at the conjunction of their fields. They argue that financial decisions of the firm can affect real economic activity-and this is true for enough firms and consumers to have significant aggregate economic effects. They demonstrate that important differences-asymmetries-in access to information between ""borrowers"" and ""lenders"" (""insiders"" and ""outsiders"") in financial transactions affect investment decisions of firms and the organization of financial markets. The original r